2010
DOI: 10.2746/042516409x475779
|View full text |Cite
|
Sign up to set email alerts
|

Equine laminitis: Induced by 48 h hyperinsulinaemia in Standardbred horses

Abstract: SummaryReasons for performing study: Hyperinsulinaemia is known to induce laminitis experimentally in healthy ponies with no history of the condition. Horses are more insulin sensitive than ponies and whether prolonged hyperinsulinaemia and euglycaemia would have a similar laminitogenic effect requires study. Objectives: To determine if laminitis results when the prolonged euglycaemic hyperinsulinaemic clamp technique (p-EHC) is applied to clinically normal Standardbred horses, and to monitor hoof wall tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
249
3
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(266 citation statements)
references
References 39 publications
10
249
3
4
Order By: Relevance
“…Since the first reports of experimental laminitis induction by prolonged systemic insulin and glucose infusion were published,5, 6 much speculation has occurred regarding the most important and relevant pathophysiologic mechanisms by which laminitis develops in this setting. Initial reports suggested that laminar IR may exist, resulting in chronic glucose (carbon substrate) deprivation at the cellular level, energy failure, and dermoepidermal separation (based on in vitro experiments using laminar explants incubated in glucose‐free media for prolonged periods and subjected to mechanical distraction) 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first reports of experimental laminitis induction by prolonged systemic insulin and glucose infusion were published,5, 6 much speculation has occurred regarding the most important and relevant pathophysiologic mechanisms by which laminitis develops in this setting. Initial reports suggested that laminar IR may exist, resulting in chronic glucose (carbon substrate) deprivation at the cellular level, energy failure, and dermoepidermal separation (based on in vitro experiments using laminar explants incubated in glucose‐free media for prolonged periods and subjected to mechanical distraction) 2.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, laminar basal epithelial cells (the cells that separate from their basement membrane during laminitis) do not appear to express the insulin receptor, suggesting that hyperinsulinemia may not directly affect these cells or may be activate alternate receptors (such as the insulin‐like growth factor‐1 receptor) 4. Although laminar energy dysregulation is thought to be involved in the pathophysiology of EMSAL,2, 5, 6 the mechanism or mechanisms involved remain poorly characterized.…”
mentioning
confidence: 99%
“…The result obtained by the authors suggests that the separation of the BM occurs secondary to initial injury, since it was possible to observe morphological changes related to the nuclei of the BC and organization of primary epidermal laminae (PEL) and secondary epidermal laminae (SEL) prior to the change of BM. de Laat et al (2010) observed the development of laminitis after insulin administration with clinical manifestation of the disease, such as hoof sensitivity and lameness, and with the histopathological assessment of the laminar tissue showing cell proliferation, thinning of SEL, rounded BC oriented perpendicular to the BM. However, these findings differ from those described by Pollitt (1996) in its classification as grade 3 associated with obvious symptoms of laminitis, such as the absence of BM and severe destruction of the lamellar architecture of the hoof.…”
Section: Discussionmentioning
confidence: 99%
“…Horses affected by Cushing's syndrome, obese animals or the ones receiving high and prolonged concentrations of glucocorticoids (RYU et al, 2004, DE LAAT et al, 2010 show endocrine disorders, such as hyperglycemia, hyperinsulinemia and insulin resistance (DE LAAT et al, 2010). The endochrinopathy laminitis is evidenced by milder clinical signs in comparison with laminitis secondary to inflammatory diseases, and in some animals it may occur rotation of the distal phalanx with hoof structural changes, with less intense painful discomfort which can be inconspicuous or absent (JOHNSON, 2002a).…”
Section: Endocrine and Metabolic Mechanismsmentioning
confidence: 99%
“…The disease can also be induced in healthy horses via insulin administration (DE LAAT et al, 2010), in an experimental model related to secondary laminitis to endocrine changes. BELKNAP et al (2011) ischemia can also promote lesions in the laminar tissue (RIO TINTO et al, 2004;LASKOSKI et al, 2010), which is supported by severe changes in laminar tissue reported in horses with natural colic syndrome not yet evidencing clinical signs of foot disease (LASKOSKI et al, 2009).…”
Section: Experimental Models Of Laminitis Inductionmentioning
confidence: 99%